The Architecture of Insecurity: A Sociological Analysis of Kidnapping and Banditry in Etsako West LGA, Edo State, Nigeria - Enaikele, Mohammed D. (NIU Journal of Social Sciences; Vol 11 No 4 (2025): NIU Journal of Social Sciences, Vol. 11 No. 4, December 2025, 2025)
Etsako West Local Government Area (LGA) in Edo North Senatorial District has, in recent years, experienced rising incidence of kidnapping and banditry, particularly along major transit corridors. This study investigates the prevalence and impacts of the insecurity between February 2022 and August 2025, using purposive sampling.  The study used secondary and primary source of data collection. Data were gathered through key informant interviews with community leaders and traditional rulers as well as unstructured in-depth interviews with farmers, traders, students, civil servants, religious leaders, vigilante groups, local hunters, youth groups, and transport workers union in Auchi, South Ibie, Agbede, Jattu, and Aviele. Findings reveal recurrent abductions, ransom payments, and community protests. Major hotspots identified include Auchi–Afuze–Agbede road, Auchi–Benin highway, Auchi–Okpella road, and Auchi–Okene–Abuja highway. The insecurity has disrupted farming, education, trade, and social life of the people. The state response through the police, DSS, and military interventions remain inadequate thereby giving rise to community policing involving vigilantes, local hunters, youth groups, and transport workers union. Yet, the insecurity persisted due to the rugged and forest terrains along the major transit routes to the neighbouring Benin, Ondo, Ekiti and Okene-Kogi State forests corridor, where the kidnappers and bandits have their forest camp/hideouts. The study recommends permanent checkpoints, sustained patrols, publicized hotlines, and combined land and aerial surveillance to effectively curb kidnapping and banditry in Etsako West LGA. Keywords: Architecture of Insecurity, Sociological Analysis, Kidnapping and Banditry, Etsako West LGA, Edo State Nigeria.